2020
DOI: 10.1111/1365-2745.13389
|View full text |Cite
|
Sign up to set email alerts
|

Optical traits perform equally well as directly‐measured functional traits in explaining the impact of an invasive plant on litter decomposition

Abstract: Functional traits can help elucidate and predict the impact of invasive plant species on ecosystem functioning. Yet, this approach requires comprehensive and labour‐intensive trait collection campaigns, covering intraspecific trait variation of both the invader and native species in the invaded community. One potential way to overcome these logistic constraints is using hyperspectral remote sensing technology to efficiently quantify functional trait values. Although such spectrally derived or ‘optical’ traits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 88 publications
0
3
0
Order By: Relevance
“…We synthesized 37 datasets from published literatures and the EcoSIS Spectral Library (https://ecosis.org/) (Hosgood et al ., 1994; Jacquemound et al ., 2003; Singh, 2013; Serbin et al ., 2014, 2017, 2018, 2019a,b,c,d, 2021; Serbin & Townsend, 2014; Couture, 2015, 2016; Couture et al ., 2015; Meerdink, 2016; Serbin, 2016; Serbin & Rogers, 2016; Yang et al ., 2016; Kattenborn et al ., 2017; Wu et al ., 2017, 2019a,b,c; Ely et al ., 2018, 2019; Kamoske et al ., 2018; Chlus, 2019; Ge et al ., 2019; Nakaji et al ., 2019; Wang, 2019a,b, 2022; Grzybowski et al ., 2020; Helsen et al ., 2020a,b; Burnett et al ., 2021a,b,c,d; Villa et al ., 2021a,b; Chen et al ., 2022; Chlus & Townsend, 2022a,b; Kothari et al ., 2022a,b,c), compiling a new dataset that covers all major biomes and climate zones over the world (Fig. 1a, Supporting Information Fig.…”
Section: Methodsmentioning
confidence: 99%
“…We synthesized 37 datasets from published literatures and the EcoSIS Spectral Library (https://ecosis.org/) (Hosgood et al ., 1994; Jacquemound et al ., 2003; Singh, 2013; Serbin et al ., 2014, 2017, 2018, 2019a,b,c,d, 2021; Serbin & Townsend, 2014; Couture, 2015, 2016; Couture et al ., 2015; Meerdink, 2016; Serbin, 2016; Serbin & Rogers, 2016; Yang et al ., 2016; Kattenborn et al ., 2017; Wu et al ., 2017, 2019a,b,c; Ely et al ., 2018, 2019; Kamoske et al ., 2018; Chlus, 2019; Ge et al ., 2019; Nakaji et al ., 2019; Wang, 2019a,b, 2022; Grzybowski et al ., 2020; Helsen et al ., 2020a,b; Burnett et al ., 2021a,b,c,d; Villa et al ., 2021a,b; Chen et al ., 2022; Chlus & Townsend, 2022a,b; Kothari et al ., 2022a,b,c), compiling a new dataset that covers all major biomes and climate zones over the world (Fig. 1a, Supporting Information Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Concerning R. rugosa, Zhang et al [50] showed that the invasive population in Germany outperformed the native population in China in terms of reproductive traits (i.e., seed production) and growth traits (i.e., shrub size), but some introduced populations appeared to be more successful invaders than others. The study by Helsen et al [51] also pointed out that R. rugosa had limited trait overlap with the invaded plant community where it is invasive: on average, it contributed to the functional space of the community introducing highly conservative leaf economic traits and strong light-competition related traits. A more recent study by Helsen et al [52] provided a comparison based on five functional traits related to the leaf economics spectrum (specific leaf area (SLA), leaf dry matter content (LDMC), leaf nitrogen content (N), phosphorous content (P), potassium content (K)) and two traits related to light-competition ability (plant height and leaf area) between individuals of R. rugosa collected in Belgium (invaded range) and those surveyed in Japan (native range).…”
Section: Functional Characteristics Of Rosa Rugosa In Invaded and Nat...mentioning
confidence: 99%
“…Leaf spectroscopy is widely used to assess foliar properties in situ, with many applications in agriculture, forestry and ecology (Asner and Martin 2009;Asner et al 2017;Chavana-Bryant et al 2017;Martin et al 2018;Wu et al 2017). Leaf spectra have been used to characterise a number of leaf physiochemical traits Asner et al 2014;Chavana-Bryant et al 2017;Nunes et al 2017;Serbin et al 2019;Wu et al 2017;Wu et al 2019), to predict ploidy levels (Blonder et al 2019), to estimate leaf age (Chavana-Bryant et al 2017;Wu et al 2017), and even to predict the impact of an invasive plant on litter decomposition (Helsen et al 2020). Importantly, leaf spectra measured in the field provide key insights into hyperspectral imagery collected from aircraft, providing underpinning data that contribute to maps of leaf traits and the functional diversity at regional scales (Asner et al 2016;Asner et al 2017;Dahlin et al 2013;Kamoske et al 2021;Knyazikhin et al 2013;Schimel et al 2013;Singh et al 2015;Wang et al 2020), and to improved understanding of the impacts of climate change (Doughty et al 2018), pests and diseases (Fallon et al 2020), and logging (Nunes et al 2021;Swinfield et al 2020).…”
Section: Introductionmentioning
confidence: 99%